MARRY POPE OSBORNEâS INFORMATION IN HER DIARY âMY SECRET WARâ: FROM THE MOOD ANALYSIS PERPECTIVE - Egar, Ngasbun (ETERNAL, 2010)
ABSTRACT Â  This paper concerns the Mood Analysis on My Secret War, a Diary written by Marry Pope Osborne. This analysis aims at: 1) identifying the Mood Structures realized in the diary and 2) describing the Finite verbal operators used in the text. The data was collected by using documentary method. The data analysis was done by a) âcoping downâ sentences into clauses, b) identified the Subject and the Finite to find out the Mood structure and c) identified the Residue. From the analysis, it was found that the types of Mood in the text mostly use declarative mood and the Finite verbal operators used in the text are mostly past temporal operators. Here the writer tells her past experience. Â  Key words: analysis, Mood, diary